A Systematic Pan-Cancer Analysis of CASP3 as a Potential Target for Immunotherapy - Zhou, Zheng; Xu, Shiying; Jiang, Liehao; Tan, Zhuo; Wang, Jiafeng (Frontiers in Molecular Biosciences, 2022)
CASP3 is the gene encoding caspase-3, a specific protease that cleaves substrates, such as poly-ADP ribose polymerase and acetyl-DEVD-7-amino-4-methylcoumarin. This enzymatic activity leads to DNA fragmentation, which is a hallmark of apoptosis. Although recent studies have demonstrated that CASP3 plays a vital role in tumour suppression by promoting apoptosis, these reports did not consider systematic pan-cancer analyses. Therefore, we performed a specific pan-cancer analysis using the Cancer Genome Atlas and Genotype-Tissue Expression databases to analyse CASP3 expression in light of cancer prognosis, DNA methylation status, tumour mutative burden (TMB), microsatellite instability (MSI), as well as immune cell infiltration in different tumours and underlying molecular mechanisms. We found that CASP3 expression was significantly associated with the prognosis of most tumours. Additionally, promoter methylation status was associated with CASP3 expression in bladder urothelial carcinoma, oesophageal carcinoma, kidney renal clear cell carcinoma, kidney renal papillary cell carcinoma, lung squamous cell carcinoma, prostate adenocarcinoma, sarcoma, testicular germ cell tumours, and uterine corpus endometrial carcinoma. TMB and MSI were associated with CASP3 expression in 15 tumours. Moreover, CASP3 expression was correlated with the tumour microenvironment in nearly all tumour types. Further, we observed that in addition to apoptosis, CASP3 action plausibly involves B cell activation, antigen presentation, immune responses, chemokine receptors, and inflammatory function. Our study thus provides a relatively comprehensive understanding of the carcinogenicity of CASP3 in different tumours, and suggests that CASP3 is a potential immunotherapy prognostic marker.